La Ley 24.309 de Necesidad de Reforma Constitucional : Análisis a la luz de los fallos "Fayt" y "Schiffrin" de la Corte Suprema de Justicia de la Nación - Chicata Campos, Ignacio Federico (2019)
Abstract: The interpretations that the National Supreme Court of Justice has done in its different compositions about the legality and scopes of the modifications to some articles of the National Constitution, executed by the constituent assembly during the 1994 reform, yet continues raising disputes in the argentine juridical doctrine. Because of the 25th anniversary of that constitutional reform, I will make a brief explanation about how the Maximum Tribunal resolved two cases (by the judgments "Fayt" and "Schiffrin"), about the irremovability of the federal magistrates in their functions, and how the act N° 24.309, that declared the necessity of the reform, has allowed -or not, in any case- an alteration in the fundaments of judges' independence principle.